Analogous corticosteroids, 9A and EK100, derived from solid-state-cultured mycelium of Antrodia camphorata inhibit proinflammatory cytokine expression in macrophages. (August 2018) - Kao, Shung-Te; Kuo, Yueh-Hsiung; Wang, Shulhn-Der; Hong, Hong-Jye; Lin, Li-Jen
Graphical abstract: Highlights: Solid-state-cultured mycelium of Antrodia camphorata (SCMAC) has anti-inflammatory effects. SCMAC extract decreased Der p-induced airway hyperresponsiveness and total serum IgE levels in mice. Compounds 9A and EK100 from SCMAC extract inhibited IL-1 β and IL-6 expression in macrophages. Abstract: Antrodia camphorata mycelium is used in traditional Chinese medicine in Taiwan. The wild-type mycelium is rare and expensive, so a solid-state-cultured mycelium of A. camphorata (SCMAC) has been developed. Previous studies have found SCMAC to have anti-inflammatory effects. However, the immunomodulatory effects of SCMAC and of its active phytosterol compounds EK100 and 9A on asthma remain unknown. In this study, BALB/c mice were repeatedly exposed to Dermatogoides pteronyssinus (Der p) at 1-week intervals and were orally administered crude SCMAC extract before the Der p challenge. The mice were sacrificed 72 h after the last challenge to examine the airway remodeling, inflammation, and expression profiles of cytokines and various genes. Then, 30-µg/mL Der p-stimulated MH-S cells with 9A or EK100 were collected for real-time PCR analysis, and the effects of 9A and EK100 on macrophages were evaluated. The crude extract reduced Der p-induced airway hyperresponsiveness, total serum immunoglobulin E levels, and recruitment of inflammatory cells to the bronchoalveolar lavage fluid through cytokine downregulation and Th1/Th2/Th17 response modulation. Additionally, 9A and EK100 inhibited IL-1β and IL-6 expression in alveolar macrophages. These results indicate that the pharmacologically active compounds in a crude SCMAC extract exert synergistic effects on multiple targets to relieve asthma symptoms.